Análisis costo beneficio de un sistema híbrido de calentamiento de agua utilizando energía solar y eléctrica para uso doméstico - Hernández Crespo, Xavier Andrés (2017)
The present project aims to make a cost-benefit analysis of a hybrid water heating system for domestic use, using solar energy and an auxiliary support system that uses electrical energy for its operation, completely eliminating the use of liquefied gas of petroleum (LPG), which is currently the most used method for heating sanitary water even though it is not the most efficient, the present will be used in a family of 4 people and will be located in the northern sector of the city of Quito. In order to be able to carry out the design and construction, 4 chapters will be considered in total, in which each element will be useful for the correct realization of the present project, being detailed each one of them as follows: - Chapter 1, presents Ecuador's current conditions in solar radiation, electricity consumption, consumption of liquefied petroleum gas and the environmental impact that is currently occurring, important concepts that will help to understand the developed research process, an analysis is available of alternatives that qualitatively evaluate the different options and select the best alternative. - Chapter 2, contains the different calculations related to the design of the project making it more optimal for the needs presented, such as the theoretical radiation in the site where the system will be located, the different energy losses among other data obtained theoretically. - Chapter 3, are evaluated the results obtained through the process of operating the system considering it as the test time, which has the purpose of observing the different behaviors presented throughout the system performance. - Chapter 4, presents a cost-benefit analysis of the system, the values that implement the system, and demonstrating the feasibility that the project will be considered as the most optimal method for different conditions presented. Completing these chapters, the proposed objectives can be achieved and demonstrate that the project is optimal for its use.